PRESPEKTIF HUKUM PIDANA DALAM MEMPERDAGANGKAN SPIRIT DOLL DI MEDIA SOSIAL - Nofaziah Eky Pratiwi; Otto Yudianto (Gapenas Publisher, 2023)
Cultural diversity is a reality that has existed throughout history in human life. Cultural diversity or what is called cultural diversity is a necessity that exists on Indonesian soil. Cultural diversity in Indonesia is something that cannot be denied and historically the Indonesian nation has a variety of cultural diversity in it. Cultural diversity gives birth to customs and beliefs. There are various types and variations in beliefs that grow among the community, both in the form of rituals or in the form of offering ceremonies, belief in spirits, and dealing with sacred objects that store supernatural energy. One example is belief in amulets. In this research, I will explain about amulets that are packaged very cute and have many forms, functions and so on. This modern talisman is known as a spirit doll